Pengaruh Model Pembelajaran Jigsaw Berbantuan Kahoot! terhadap Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan di SMKS Raden Paku (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
This study aims to examine the effect of the Jigsaw learning model on X grade students of the Electrical Installation Engineering program at SMKS Raden Paku, enhanced with the use of the Kahoot! platform. The research employs a quantitative method with a quasi-experimental design and a nonequivalent control group design. The subjects of the study were divided into two groups: the control group, which applied the Jigsaw learning model using PowerPoint media, and the experimental group, which applied the Jigsaw model using the interactive Kahoot! media. Data were collected through pretest and posttest, as well as observation sheets to assess students' learning outcomes in the affective and psychomotor aspects. Data analysis techniques included normality test, homogeneity test, paired sample t-test, independent sample t-test, and normalized gain (N-Gain) analysis. The findings showed that the average learning outcomes difference between the control group (71.5%) and the experimental group (72.3%) was in the moderately effective category. However, the use of the Jigsaw learning model with Kahoot! had an effect on student learning outcomes, but the influence was not very large. This study provides insights into the effectiveness of using Kahoot! in the Jigsaw learning model.